Rural Marketing in India-An Over view: Case Study of BSNL (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2006)
The growing complexities in the modern marketing are also generating ample opportunities in the business world and it has become important for the producers of goods and services to tap all such markets where enough untapped potential is available. The dynamic change in the marketing practices and strategies has transformed the marketing environment to a significant extent. To meet the challenge of creation and retention of customers and entry to rural market with good product packages has become need of an hour. On the other hand increased purchasing power of rural customers has attracted the attention of marketers. It requires unique marketing strategy full of client and location oriented involvement of 4A’s. Keeping in view the growth and development of rural markets in India which are contributing significantly in the country’s GDP and contributes more than 50% in the total sales of durable and non durable products. It has become more important to look in to the rural markets with great zeal and enthusiasm. Organizations need to sustain if effective network is available to adopt neo-marketing strategies to tap such markets available in rural and for flung areas where more than 65% population is residing with large untapped consumer potential. For this the role of telecom service providers cannot be overlooked. Present paper is an attempt to overview the concept of rural marketing for which marketing strategy with 4-A approach is applied on BSNL one of the leading telecommunication service provider in rural India and to analyze their various marketing strategies adopted for rural customers.